Eosinophilic Granulomatosis with Polyangiitis in an 8-year-old Girl Manifesting as Hypereosinophilic Syndrome with Myocarditis, Stroke, and Subsequent Orbital Involvement - Paņina, Aleksandra; Ligere, Elīna; Aleksejeva, Elīna; Davidsone , Zane; Cebura, Elizabete; Erdmane, Irina (Acta medica Lituanica, 2023)
Hypereosinophilic syndrome (HES) is a heterogeneous group of disorders characterized by peripheral blood eosinophilia of 1.5 × 109/L (1,500/μL) or greater, with evidence of end-organ damage attributable to eosinophilia (e.g., heart, liver or lung) with no other cause for the end-organ damage [1]. Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare disorder that may affect multiple organ systems (lungs, heart, kidneys, or the nervous system). The disorder is characterized by hypereosinophilia in the blood and tissues, inflammation of blood vessels (vasculitis), and the development of inflammatory nodular lesions called granulomatosis [2]. We report a case with a 9-year-old girl presenting with severe hypereosinophilia, ischemic stroke, right-sided hemiparesis and myocarditis treated with methylprednisolone, enoxaparin, rivaroxaban and carvedilol. The patient recovered successfully from myocarditis and stroke but manifested with right-sided orbital involvement as pre- and post-septal orbital cellulitis 10 months later with necrotizing granulomatous perivascular chronic infiltration with eosinophilic infiltration treated with methylprednisolone and subsequent mepolizumab with successful remission of orbital involvement, but severe exogenous Cushing’s syndrome and myocardial fibrosis.